Design of large π-conjugated α-cyanostilbene derivatives as colorimetric sensors for volatile acids and organic amine gases. Issue 12 (24th February 2020) - Cao, Xinhua; Li, Yiran; Han, Qingqing; Gao, Aiping; Wang, Bingya; Chang, Xueping; Hou, Ji-ting
Abstract : Two large π-conjugated α-cyanostilbene derivative isomers (M-PDC and P-PDC ) could sensitively and continuously detect volatile acids and organic amine gases. Abstract : Two large π-conjugated α-cyanostilbene derivatives (2 Z, 2′ Z, 4 E, 4′ E )-2, 2′-(1, 3-phenylene)bis(5-(4-(dimethylamino)phenyl)penta-2, 4-dienenitrile) (M-PDC ) and (2 Z, 2′ Z, 4 E, 4′ E )-2, 2′-(1, 4-phenylene)bis(5-(4-(dimethylamino)-phenyl)penta-2, 4-dienenitrile) (P-PDC ) were designed and synthesized through a Knoevenagel condensation reaction between m -phenylenediacetonitrile, p -phenylenediacetonitrile and 4-(dimethylamino)cinnamaldehyde. The two α-cyanostilbene derivatives were isomers, and their optical properties including absorption, emission, quantum yields and lifetime could be tuned by the isomer effect. P-PDC showed an absorption band and an emission peak all at larger wavelengths than M-PDC under the same conditions. Compared to M-PDC, P-PDC exhibited a higher fluorescence quantum yield. Theoretical calculations demonstrated that P-PDC possessed a larger π-conjugated system than M-PDC based on the density functional theory (DFT) method. M-PDC and P-PDC with two dimethyl amine units as proton binding sites showed sensitive naked eye detection ability toward some volatile acids with certain acidity. For example, the limits of detection of solutions of M-PDC and P-PDC in CH2 Cl2 were 2.0 and 8.82 nM. Solutions of M-PDC and P-PDC in CH2 Cl2 with the addition of TFA could detect some organic amines, and the limits of detection towards TEA were 1.76 and 3.47 nM. Solutions of M-PDC and P-PDC in CH2 Cl2 were coated onto a quartz plate and formed a film with different morphologies, which emitted very weak light due to the ACQ effect. But, fortunately, the ACQ effect in the M-PDC and P-PDC films could be overcome via the introduction of CTAB and they exhibited great fluorescence enhancement by 225-fold and 105-fold, respectively. These results enabled a response towards volatile acid gases. The limit of detection of the M-PDC and P-PDC films towards TFA was 17.4 and 2.37 ppm. The M-PDC and P-PDC films showed good reversibility by contacting with volatile acids and organic amine gases in turn. This research will provide a new route for the construction of functional large π-conjugated systems for the detection of gaseous acids and organic amines.